Liprin-α4 is a new hypoxia-inducible target gene required for maintenance of cell-cell contacts - Mattauch, Sandra; Sachs, Martin; Behrens, Jürgen (Experimental Cell Research, 2010)
Liprin-α1 to liprin-α4 constitute a family of cytoplasmic proteins, which have been found in various multiprotein complexes. For liprin-α1 roles in synapse formation and cell spreading were described but other liprin family members are not well characterized. We show here that liprin-α4 is upregulated in human clear cell renal cell carcinomas (RCC) as compared to normal kidney tissue. Liprin-α4 expression is downregulated by the von Hippel-Lindau tumor suppressor (VHL) and upregulated by hypoxia in RCC cell lines. The liprin-α4 gene promoter is directly activated by binding of the hypoxia-inducible factor 1α (HIF-1α) to HRE consensus binding sites as shown by reporter assays and chromatin immunoprecipitations. RNAi mediated knockdown of liprin-α4 leads to reduced E-cadherin and Β-catenin levels at cell junctions and to dissociation of epithelial cell contacts. Our data describe for the first time liprin-α4 as a hypoxia-induced gene potentially involved in cell-cell adhesion. © 2010 Elsevier Inc.
Created from Fastlane, Scopus look-up
Keywords: Cell-cell contacts; E-cadherin; HIF; Liprin; RCC; VHL